Private label shoppers between fast fashion trends and status symbolism – A customer characteristics investigation. (January 2020) - Bockholdt, Katrin; Kemper, Jan; Brettel, Malte
Abstract: The question who the private label prone consumer is has received a lot of attention in research. While we so far have a good understanding of the private label shopper in the grocery industry, there is limited research in other industries. We assess private label shopper characteristics as a driver of private label choice using a unique data set of an online only fashion retailer covering 68, 147 women shoes consumers in Germany. Fashion consumers are faced with a tradeoff between price and seasonality of fashion items as discounts are used to sell last season's stock. We find that private label choice is positively influenced by price orientation and less by discount proneness. Thus, private label shoppers are rather a fashion savvy segment focusing on buying more in season but at a lower price.